Direct Effects of Vitamin D Supplementation on Ultramarathon-Induced Changes in Kynurenine Metabolism - Mieszkowski, Jan; Brzezińska, Paulina; Stankiewicz, Błażej; Kochanowicz, Andrzej; Niespodziński, Bartłomiej; Reczkowicz, Joanna; Waldziński, Tomasz; Kacprzak, Bartłomiej; Siuba-Jarosz, Natalia; Petr, Miroslav; Antosiewicz, Jędrzej (Nutrients, 2022)
In humans, most free tryptophan is degraded via kynurenine pathways into kynurenines. Kynurenines modulate the immune system, central nervous system, and skeletal muscle bioenergetics. Consequently, kynurenine pathway metabolites (KPMs) have been studied in the context of exercise. However, the effect of vitamin D supplementation on exercise-induced changes in KPMs has not been investigated. Here, we analyzed the effect of a single high-dose vitamin D supplementation on KPMs and tryptophan levels in runners after an ultramarathon. In the study, 35 amateur runners were assigned into two groups: vitamin D supplementation group, administered 150,000 IU vitamin D in vegetable oil 24 h before the run (n = 16); and control (placebo) group (n = 19). Blood was collected for analysis 24 h before, immediately after, and 24 h after the run. Kynurenic, xanthurenic, quinolinic, and picolinic acids levels were significantly increased after the run in the control group, but the effect was blunted by vitamin D supplementation. Conversely, the decrease in serum tryptophan, tyrosine, and phenylalanine levels immediately after the run was more pronounced in the supplemented group than in the control. The 3-hydroxy-l-kynurenine levels were significantly increased in both groups after the run. We conclude that vitamin D supplementation affects ultramarathon-induced changes in tryptophan metabolism.
Keywords: Kynurenine; centrální nervový systém; potravní doplňky; lidé; kynurenin; vitamin D; kynurenine; ultramarathon; Central Nervous System; Humans; skeletal muscle damage; tryptofan; Tryptophan; Vitamin D; Dietary Supplements